Effect of IoT Integration in Energy Management System and Grid Responsiveness on Energy Efficiency and Cost Reduction in Jakarta Government Buildings - Hetty Rohayani; Ermaini Ermaini; Rahmi Handayani; Rifky Lana Rahardian; Agi Nanjar (Westscience Press, 2024)
This study investigates the effect of IoT integration in energy management systems (EMS) and network responsiveness on energy efficiency and cost reduction in DKI Jakarta government buildings. A quantitative analysis was conducted using structural equation modeling (SEM) with Partial Least Squares (PLS) 3. Survey questionnaires were administered to building managers, energy engineers, and facility maintenance personnel, while energy consumption data were obtained from relevant authorities. The results demonstrate a significant positive impact of both IoT integration and network responsiveness on energy management outcomes. Specifically, Energy Management System (EMS) and Grid Responsiveness were found to significantly influence both Cost Reduction and Energy Efficiency within government buildings. These findings have important implications for policymakers, building managers, and stakeholders involved in energy management decision-making. By leveraging advanced energy management technologies and practices, DKI Jakarta government buildings can achieve significant cost savings, improve energy efficiency, and advance environmental sustainability.